Robotic distal gastrectomy using a novel pre-emptive supra-pancreatic approach without duodenal transection in the dissection of D2 lymph nodes for gastric cancer - Xie, Jianming; Yang, Jiabin; Wang, Meixiao; Yin, Yongfang; Yan, Zhilong (Frontiers in Oncology, 2024)
Background: Robot-assisted surgery is demonstrating remarkable progress as a minimally invasive procedure for gastric cancer. This study aims to compare the pre-emptive supra-pancreatic approach without duodenal transection and the conventional approach in terms of perioperative feasibility and short-term surgical outcomes.We retrospectively analysed all patients who underwent robotic distal gastrectomy with D2 lymph node dissection using the da Vinci Xi robotic system between December 2021 and April 2023, categorising them into two groups for comparison. Patients treated using the pre-emptive supra-pancreatic approach (observation group) were compared with those who received the conventional approach (control group). Employing one-to-one propensity score matching, we evaluated postoperative morbidity and short-term outcomes in these two distinct groups to assess the efficacy and safety of the novel surgical technique.Results: This study enrolled 131 patients, 70 in the observation group and 61 in the control group. After propensity score matching, the operative times were significantly longer in the control group than in the observation group (229.10 ± 33.96 vs. 174.84 ± 18.37, p < 0.001). The mean blood loss was less in the observation group than in the control group (25.20 ± 11.18 vs. 85.00 ± 38.78, p < 0.001). Additionally, the 3 observation group exhibited a higher number of retrieved lymph nodes, including suprapyloric, perigastric and superior pancreatic lymph nodes (28.